Experimental validation of CFD simulations of free-fall lifeboat launches in regular waves. Issue 3 (October 2015) - Berchiche, Nabila; Östman, Anders; Hermundstad, Ole Andreas; Reinholdtsen, Svein-Arne
Abstract : This paper presents results from model tests and CFD simulations of lifeboat launches in regular waves. To the authors' knowledge, this is the first time CFD simulations of lifeboat launches in waves have been validated. The predicted accelerations agreed well with the measured ones. The pitch velocity was slightly overestimated due to a slight difference in the geometric features at the bow between the CFD model and the physical model. The simulations provided in general accurate or conservative estimates of the local pressure at various locations on the hull except on one location on top of the canopy where the pressure was slightly under-predicted. Furthermore, it has been shown that to improve the predictions of the pressure loads on the aft wall of the lifeboat, the compressibility of air has to be taken into account in the simulations in order to capture the behaviour of the air-pocket behind the lifeboat.